Dose-dependent effects of cholecalciferol supplementation on hepatocyte ballooning in Sprague–Dawley rats - Veonika, Dea Anenta (PT. Mega Science Indonesia, 2025)
Obesity is an accumulation of fat body condition due to calories and energy imbalance. Low vitamin D levels are also associated with lower HDL levels, increased triglyceride levels, and increased triglyceride deposition levels in hepatocytes and liver parenchyma. Vitamin D supplementation has various benefits for obesity, such as by improving lipid profiles, reducing BMI, reducing waist circumference, and reducing hip circumference. This study aims to analyze the histopathological changes in the liver of male rats induced by a high-fat, high-fructose diet and supplemented with cholecalciferol. Thirty male Sprague-Dawley rats aged 6-8 weeks were randomly allocated into 5 groups. The normal control (KN) group only received the BR-2 pellet and PAM ad libitum. The negative control (K-) group received a high-fat, high-fructose diet (HFHF) for 28 days. The P1 group received only HFHS for the first 28 days and was supplemented with cholecalciferol 2500 IU thereafter. The P2 group received only HFHF for the first 28 days and was supplemented with cholecalciferol 5000 IU thereafter. The P3 group received only HFHF for the first 28 days and was supplemented with cholecalciferol 10000 IU thereafter. Histopathological analysis involves analyzing the microscopic image of the liver tissue of the obese rat models after receiving treatment with cholecalciferol for 56 days. After 8 weeks of intervention, cholecalciferol supplementation resulted in different findings on histopathological analysis. After intervention with cholecalciferol, there is no significant difference in the degree of steatosis and lobular inflammation on rat liver histopathology (p>0.05). Cholecalciferol supplementation resulted in a significant difference in hepatocyte ballooning on liver histopathology (p<0.05). Administration of cholecalciferol at doses of 2,500 IU, 5,000 IU, and 10,000 IU was not significant in improving liver steatosis and lobular inflammation, but could reduce the occurrence of liver ballooning